Parallel machine scheduling with tool loading: a constraint programming approach - Gökgür, Burak; Hnich, Brahim; Özpeynirci, Selin (International journal of production research, 2018)
This paper presents constraint programming models that aim to solve scheduling and tool assignment problems in parallel machine environments. There are a number of jobs to be processed on parallel machines. Each job requires a set of tools, but limited number of tools are available in the system due to economic restrictions. The problem is to assign the jobs and the required tools to machines and to determine the schedule so that the makespan is minimised. Three constraint programming models are developed and compared with existing methods described in the literature.